Effects of various feed forms on some gut bacteria and subsequent effects on productivity, egg quality, and intestinal morphology in indigenous laying hens - Zahira A. AL-Zuhairi; Esraa T. Muslim; Shaimaa Abbas Sabeeh; Orooba Meteb Faja (Open Veterinary Journal)
Background: Local hen layers play a crucial role in egg production and the poultry industry. Optimizing their performance, egg quality, and overall health is of paramount importance.